Endemic, outbreak or epidemic?: Geographies of affliction, exposure and homicide immunity in Chicago - Ferrandino, Joseph (Journal of crime and justice, 2018)
Chicago is a historically violent city. After years of homicide reduction and/or relative stability in homicides, the Windy City is experiencing what is being described as a ‘homicide epidemic’ starting in 2016. This study analyzes Chicago homicides from 2001 to 2016 (n = 8132) epidemiologically. A long-term annual epidemiological curve establishes homicide likely reaching epidemiological levels at the macro (city) and micro (block group) levels amidst outbreaks and spreading exposure. Geospatial analysis revealed 14 census block groups (of 2513) that were immune from homicide for 15 years yet adjacent to highly afflicted block groups. A series of one-sample tests reveal these block groups to be the most diverse in the city have less favorable demographics (greater percentage of males aged 7-20) and economic indicators (significantly more households below $50 K/year, higher poverty and higher unemployment) and an equivalent environment to the other immune groups. On all the indicators, the immune/adjacent blocks had more favorable indicators than exposed and afflicted areas and provide a place to better understand what innoculates or immunizes these areas from such a widespread social affliction they are so closely exposed to.